The movie of the week : private stories/public events - Rapping, Elayne, 1938- (American culture (Minneapolis, Minn.), 1992)
Here's a sophisticated, against-the-grain study of the politics of popular TV by Elayne Rapping. The essays in this work focus on a particular genre: the made-for-TV movie, which is usually dismissed as schmaltzy, low-brow, vacuous, apolitical fare by contemptuous critics. But Rapping takes on this prevailing elitist attitude; she defends many of these movies for being public events that wrestle with urgent social issues, and she argues that they often carry progressive, even subversive, messages, albeit in a contradictory way.